Sex Trafficking of Minors: The Impact of Legislative Reform and Judicial Decision Making in Metropolitan and Non-Metropolitan Communities, Kentucky, 2007-2018 - Cole, Jennifer ([Verlag nicht ermittelbar], 2019)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study includes data that was used to investigate the effect of legislative and judicial factors on system responses to sex trafficking of minors (STM) in metropolitan and non-metropolitan communities. To accomplish this, researchers evaluated the effectiveness of the immunity, protection, and rehabilitative elements of a state safe harbor law. This project was undertaken as a response to a growing push to pass state safe harbor laws to align governmental and community responses to the reframing of the issue of sex trafficking of minors that was ushered in with the passage of the Trafficking Victims Protection Act (TVPA). This collection includes 4 SPSS files, 3 Excel data files, and 2 SPSS Syntax files: Child-Welfare-Human-Trafficking-Reports-2013-2017-data.xlsx Judicial-Interview-De-identified-Quantitative-Data-for-NACJD_REV_Oct2018.sav (n=82; 36 variables) Judicial-online-survey-data-for-NACJD_REV_Dec2018.sav (n=55; 77 variables) Juvenile-Justice-Screening-for-HT-2015-MU-MU-0009.xlsx Post-implementation-survey-data-for-NACJD_REV_Dec2018.sav (n=365; 1029 variables) Pre-implementation-survey-data-for-NACJD_REV_Dec2018.sav (n=323; 159 variables) Recode-syntax-for-pre-implementation-survey-for-NACJD.sps Statewide-juvenile-court-charges-2015-MU-MU-0009-to-NACJD.xlsx Syntax-for-post-implementation-survey-data-to-NACJD.sps Qualitative data from judicial interviews and agency open-ended responses to Post-Implementation of the Safe Harbor Law Survey are not available as part of this collection.